Copper‐Mediated Formation of Aryl, Heteroaryl, Vinyl and Alkynyl Difluoromethylphosphonates: A General Approach to Fluorinated Phosphate Mimics. (11th September 2015) - Ivanova, Maria V.; Bayle, Alexandre; Besset, Tatiana; Poisson, Thomas; Pannecoucke, Xavier
Abstract: A general and efficient access to aryl, heteroaryl, vinyl and alkynyl difluoromethylphosphonates is described. The developed methodology using TMSCF2 PO(OEt)2, iodonium salts and a copper salt provided a straightforward manifold to reach these highly relevant products. The reaction proved to be highly functional group tolerant and proceeded under mild conditions, giving the corresponding products in good to excellent yields. This method represents the first general synthetic route to this important class of fluorinated scaffolds, which are well‐recognized as in vivo stable phosphate surrogates.